Global existence and estimates of the solutions to nonlinear integral equations - Ramm, Alexander G. (Global Journal of Mathematical Analysis, 2017)
It is proved that a class of nonlinear integral equations of the Volterra-Hammerstein type has a global solution, that is, solutions defined for all \(t\ge 0\), and estimates of these solutions as \(t→ ∞\) are obtained. The argument uses a nonlinear differential inequality which was proved by the author and has broadapplications.